2012
DOI: 10.1051/0004-6361/201118735
|View full text |Cite
|
Sign up to set email alerts
|

Transient dust in warm debris disks

Abstract: Context. Debris disks trace remnant reservoirs of leftover planetesimals in planetary systems. In the past years, a handful of "warm" debris disks have been discovered in which emission in excess starts in the mid-infrared. An interesting subset of these warm debris disks shows emission features in mid-infrared spectra, which points towards the presence of μm-sized dust grains, with temperatures above hundreds K. Given the ages of the host stars, the presence of these small grains is puzzling, and raises quest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
66
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 94 publications
8
66
1
Order By: Relevance
“…It is interesting to note that only for a few debris disk sources is there solid evidence for olivine with a high (∼20%) iron fraction, suggesting that the olivine material in these debris disks originated from larger differentiated bodies (Olofsson et al 2012). This is also consistent with the recent detection of the 69 μm band in the young debris disk system β Pictoris, which shape and position is consistent with olivine with an iron fraction of at most 1% (de Vries et al 2012).…”
Section: Formation History Of the Forsterite Grainssupporting
confidence: 84%
“…It is interesting to note that only for a few debris disk sources is there solid evidence for olivine with a high (∼20%) iron fraction, suggesting that the olivine material in these debris disks originated from larger differentiated bodies (Olofsson et al 2012). This is also consistent with the recent detection of the 69 μm band in the young debris disk system β Pictoris, which shape and position is consistent with olivine with an iron fraction of at most 1% (de Vries et al 2012).…”
Section: Formation History Of the Forsterite Grainssupporting
confidence: 84%
“…Olivine and pyroxene minerals are the primary minerals in stony and stony-iron meteorites, 75% of chondrite meteorites and 50% of pallasites (Petrovic 2001;Gaffey et al 2002); (b) Mg-rich olivine (fosterite) has been detected in spectra of several cometary tails and is present in the majority of comet Wild 2 samples returned by NASA's Stardust Mission (Zolensky et al 2006); (c) parallel studies of the spectral features of the dust particles, observed in exo-planetary system β Pictoris (de Vries et al 2012), confirm similar abundance of Mg-rich olivine in respective areas (large heliocentric distances) to our Solar System; (d) Fe-rich olivine (fayalite) is mostly encountered in asteroid mineralogies (Nakamura et al 2011) and therefore in the warmer, inner parts, of planetary space (Olofsson et al 2012). Possible explanations for this distribution of the different types of olivine are: (1) the presence of water on comets which leads to aqueous alteration, as the fayalite may not survive in the presence of water (Olofsson et al 2012) and, (2) the higher abundance of heavier elements, such as Fe, in the inner Solar System; (e) Basalt is considered to be the main material on the surface of the differentiated asteroids. Differentiation, which leads to a multi-layered body with core, mantle and crust and the production of basalt, occurred in the early Solar System.…”
Section: The Projectilesmentioning
confidence: 64%
“…Defrère et al 2011), MIDI/VISIR (e.g. Smith et al 2009b), or using their mid-infrared spectra with Spitzer (Olofsson et al 2012;Lisse et al 2012Lisse et al , 2009). Such sources have been compared to the solar system's exozodiacal cloud, but in general are several orders of magnitude brighter, for example η Corvi is 1250 ± 260 times brighter than the solar system's exozodiacal dust cloud at 10 μm (Millan-Gabet et al 2011).These observations can be modelled to determine estimates on the geometry, mass, position and grain properties.…”
Section: Introductionmentioning
confidence: 99%